2013
DOI: 10.1371/journal.pone.0056221
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Hot Topic Detection in Online Communities Using Text Clustering

Abstract: Recently, health-related social media services, especially online health communities, have rapidly emerged. Patients with various health conditions participate in online health communities to share their experiences and exchange healthcare knowledge. Exploring hot topics in online health communities helps us better understand patients’ needs and interest in health-related knowledge. However, the statistical topic analysis employed in previous studies is becoming impractical for processing the rapidly increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 19 publications
3
86
2
Order By: Relevance
“…22,51,52 On the other hand, other researchers found that more online participation by support persons occurred when the prognosis for a loved one was poor or when the disease had advanced. 39 As found by Lu et al, 53 who compared topical content volunteered in breast and lung cancer online communities, users in this study also focused on informational support and appraisal of threatening new or long-standing and unrelieved symptoms such as chest pain to boost coping strategies based on advice provided by other experienced users. Information exchange was rare in this online support community and other online communities without empathic support.…”
Section: Naturalistic Conversationsmentioning
confidence: 94%
“…22,51,52 On the other hand, other researchers found that more online participation by support persons occurred when the prognosis for a loved one was poor or when the disease had advanced. 39 As found by Lu et al, 53 who compared topical content volunteered in breast and lung cancer online communities, users in this study also focused on informational support and appraisal of threatening new or long-standing and unrelieved symptoms such as chest pain to boost coping strategies based on advice provided by other experienced users. Information exchange was rare in this online support community and other online communities without empathic support.…”
Section: Naturalistic Conversationsmentioning
confidence: 94%
“…It arose from the related fields of data mining, artificial intelligence, statistics, databases, library science, and linguistics. As it is detailed in [3], since text mining is a multidisciplinary field, this term has been used to describe different applications such as text categorization [26,27], prediction [28,29], text clustering [30,31], association discovery [32,33] and finding patterns in text databases [34].…”
Section: Background and Related Workmentioning
confidence: 99%
“…36,56,67,76 Other cancers mentioned were osteosarcoma, 73 rhabdomyosarcoma, 55 testicular, 11 skin, 23 cervical, 37,53,59,65 ovarian, 21, lung, 34 and colorectal. 14,24 Cancer in general was the focus of 21 articles (30.4%),9,15,19,20,3133,38,40,44,4648,52,54,57,6264,70,72 and 11 (15.9%) discussed multiple types of cancer.…”
Section: Resultsmentioning
confidence: 99%